Retrospective Evaluation Of Incisional Hernia Occurrence Following Major Abdominal Procedures - Kumar, Prasanna; P.S, Saravanan (Journal of Neonatal Surgery, 2025)
ABSTRACT Introduction: Incisional hernias are a common postoperative complication following major abdominal surgeries, often resulting in discomfort, obstruction, and the need for additional surgical interventions. This study aimed to determine the incidence of incisional hernias and identify associated risk factors in patients undergoing major abdominal procedures. Materials & Methods: A retrospective cohort study was conducted at Territory Care Hospital from June 2023 to December 2024. Medical records of 100 patients aged ≥18 years who underwent major abdominal surgeries, including laparotomy, colorectal, and bariatric procedures, were reviewed. Data on demographics, surgical details, comorbidities, and postoperative outcomes were extracted from electronic medical records. Statistical analyses, including univariate and multivariate logistic regression, were performed using SPSS version 27.0 to identify predictors of incisional hernia. Results: The overall incidence of incisional hernia was 20%. Laparotomy had the highest incidence rate (30%), followed by colorectal surgery (20%) and bariatric surgery (6%). Patients with higher age and elevated BMI showed a trend toward increased hernia risk, though statistical significance was not achieved due to the limited sample size. Comorbidities such as diabetes (25%), hypertension (37%), and smoking (20%) were prevalent in the study population and may contribute to impaired wound healing. Conclusion: Incisional hernias remain a significant complication after major abdominal surgeries, particularly following laparotomy. Obesity and advanced age appear to be key patient-related risk factors. This study emphasizes the need for improved risk assessment, patient optimization, and surgical techniques to reduce the incidence of incisional hernias. Larger, multicenter, prospective studies are recommended to further validate these findings and inform clinical practice.